Quantitative proteomic analysis of HER2 expression in the selection of gastric cancer patients for trastuzumab treatment. (29th September 2016) - An, E.; Ock, C.-Y.; Kim, T.-Y.; Lee, K.-H.; Han, S.-W.; Im, S.-A.; Kim, T.-Y.; Liao, W.-L.; Cecchi, F.; Blackler, A.; Thyparambil, S.; Kim, W. H.; et al.
Abstract: Background: A wide range of response rates have been reported in HER2-positive gastric cancer (GC) patients treated with trastuzumab. Other HER2-targeted therapies for GC have yet to show efficacy in clinical trials. These findings raise question about the ability of standard HER2 diagnostics to accurately distinguish between GC patients who would and would not benefit from anti-HER2 therapies. Patients and methods: GC patients ( n = 237), including a subset from the Trastuzumab in GC (ToGA) trial were divided into three groups based on HER2 status and history of treatment with standard chemotherapy or chemotherapy plus trastuzumab. We applied mass spectrometry-based proteomic analysis to quantify HER2 protein expression in formalin-fixed tumor samples. Using HER2 expression as a continuous variable, we defined a predictive protein level cutoff to identify which patients would benefit from trastuzumab. We compared quantitated protein level with clinical outcome and HER2 status as determined by conventional HER2 diagnostics. Results: Quantitative proteomics detected a 115-fold range of HER2 protein expression among patients diagnosed as HER2 positive by standard methods. A protein level of 1825 amol/µg was predicted to determine benefit from the addition of trastuzumab to chemotherapy. Trastuzumab treated patients with HER2 protein levels above this cutoff had twice the median overall survival (OS) of their counterparts below the cutoff (35.0 versus 17.5 months, P = 0.011). Conversely, trastuzumab-treated patients with HER2 levels below the cutoff had outcomes similar to HER2-positive patients treated with chemotherapy. (Progression-free survival = 7.0 versus 6.5 months: P = 0.504; OS = 17.5 versus 12.6 months: P = 0.520). HER2 levels were not prognostic for response to chemotherapy. Conclusions: Proteomic analysis of HER2 expression demonstrated a quantitative cutoff that improves selection of GC patients for trastuzumab as compared with current diagnostic methods.